Optimizing Dynamic T2* MR Imaging for Measurement of Cerebral Blood Flow Using Infusions for Cerebral Blood Volume - Newman, G.C.; Hospod, F.E.; Fain, S.B.; Cook, T.D. (American Journal of Neuroradiology, 2006)
Summary: We describe an approach to measuring cerebral blood flow (CBF) based on independent measurements of cerebral blood volume (CBV) and mean transit time (MTT) with calculation of CBF by using the central volume theorem: CBF = CBV / MTT. This permits optimization of the individual acquisitions and analyses. In particular, measurement of CBV during contrast infusion, rather than simultaneously with MTT from a single bolus, yields values more consistent with those of other methods.